1990
DOI: 10.1172/jci114777
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of lovastatin therapy on the parameters of whole-body cholesterol metabolism.

Abstract: The effects of lovastatin therapy on the parameters of body cholesterol metabolism were explored in nine hypercholesterolemic patients. Long-term cholesterol turnover studies were performed before therapy, and were repeated after 15 mo of lovastatin therapy (40 mg/d) while continuing on therapy. The major question addressed was whether a reduction in plasma cholesterol level with lovastatin would be associated with a reduction in the whole-body production rate of cholesterol or with the sizes of exchangeable b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 33 publications
3
28
1
Order By: Relevance
“…Sterol balance measurements in humans treated with pravastatin showed slight decreases in cholesterol synthesis (13)(14)(15). In contrast, Goldberg et al (16) found that cholesterol synthesis rates were unaltered in lovastatintreated patients. Kallien et al (17) measured cholesterol synthesis in human subjects treated with pravastatin or placebo in a direct way using 13 C-acetate, which is incorporated into the cholesterol molecule during cholesterol synthesis.…”
Section: C-acetate Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Sterol balance measurements in humans treated with pravastatin showed slight decreases in cholesterol synthesis (13)(14)(15). In contrast, Goldberg et al (16) found that cholesterol synthesis rates were unaltered in lovastatintreated patients. Kallien et al (17) measured cholesterol synthesis in human subjects treated with pravastatin or placebo in a direct way using 13 C-acetate, which is incorporated into the cholesterol molecule during cholesterol synthesis.…”
Section: C-acetate Methodsmentioning
confidence: 89%
“…The effects on biliary secretion may indicate inhibition of hepatic cholesterol synthesis in humans. However, the few early studies in statin-treated humans that applied direct methods to measure cholesterol synthesis and failed to prove a reduced cholesterol synthesis (16) or even pointed toward increased cholesterol synthesis (17) indicate that whole body cholesterol synthesis may also be augmented in humans. If increased cholesterol synthesis after statin treatment is also the case in humans, then it would be important to investigate whether this would also lead to enhanced fecal excretion of neutral sterols or if the newly synthesized cholesterol undergoes a different fate.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, any possible limitation of MIDA will not invalidate any of our conclusions, because these were drawn from intraindividual comparisons and the pool size was shown not to change after an HMG-CoA reductase inhibitor. 25 After pravastatin administration, the fractional synthesis in plasma (4.0%) was in the range of placebo values. Also, absolute cholesterol synthesis of the body was comparable after placebo and pravastatin treatment with an unchanged decay rate constant (turnover rate) of plasma cholesterol.…”
Section: Discussionmentioning
confidence: 94%
“…In previous studies, cholesterol synthesis after long-term inhibition of the HMG-CoA reductase in humans was variably suppressed or unchanged. 22,25,27,28,38,[45][46][47][48] This was more pronounced (Ϫ29% to Ϫ64%) if indirect indicators of body cholesterol synthesis like serum lathosterol, 24,26,45,46 urinary mevalonate, 47,48 or cholesterol synthesis in mononuclear leukocytes 22,38 were used. In comparison, only minor effects (ϩ7% to Ϫ18%) have been observed using the more quantitative estimation by the sterol balance technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation